Pengaruh Inovasi Produk dan Strategi Pemasaran Terhadap Keputusan Pembelian Konsumen Kuliner - Alfon Tuhoni Zebua; Paul Karolus Pasaribu, Johni; Naibaho, Ronald (Journal of Trends Economics and Accounting Research, 2024)
The impact of product innovation and marketing tactics on customer purchase decisions will be covered in this study. This study sought to ascertain how, if at all, product innovation and marketing tactics influenced consumers' decisions to buy. This kind of research is quantitative, and the 97 participants in the study made up the sample. Techniques for gathering data include surveys, questionnaires, observation, and documentation. The data analysis method used in this study includes multiple linear regression analysis, descriptive analysis, and classical assumption tests such as the multicollinearity, heteroscedasticity, and F tests as well as coefficient of determination and t tests with SPSS. The study's findings suggest that product innovation influences consumers' decisions to buy to some extent. Purchasing decisions are not partially influenced by marketing strategy. Meanwhile, at the Javas Cycle café in Jambi City, customers' decisions to buy are influenced by both marketing strategy and innovative products.